RUMAH TANGGA SEBAGAI SALAH SATU WADAH PENDIDIKAN - Musdalifa Musdalifa (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2007)
Family is the first and primary place for children’s moral education. A child is born without having any strength except the love of his or her family becomes a resource of life. The children’s growth and development is very dependent on other people, particu-larly his or her parents. The basis of education is given through this environment that goes based on the norms in society. The basis of psychological experiences is taught through mercy and love. The needs about the authority and moral value are integrated into the attitude and behavior as the example of the children’s moral development. Considering position of the family that is very important in the children’s moral development, the involvement and attention of all parts especially the academic practitioner to comprehensively study in order to become a good reference for the family to lead and develop children’s moral education.